Re-Emergence of Minimal Residual Disease Detected by Flow Cytometry Predicts an Adverse Outcome in Pediatric Acute Lymphoblastic Leukemia - Wang, Yu; Xue, Yu-Juan; Jia, Yue-Ping; Zuo, Ying-Xi; Lu, Ai-Dong; Zhang, Le-Ping (Frontiers in Oncology, 2021)
Purpose: While the role of minimal residual disease (MRD) assessment and the significance of achieving an MRD-negative status during treatment have been evaluated in previous studies, there is limited evidence on the significance of MRD re-emergence without morphological relapse in acute lymphoblastic leukemia (ALL). We sought to determine the clinical significance of MRD re-emergence in pediatric ALL patients. Methods: Between 2005 and 2017, this study recruited 1126 consecutive patients newly diagnosed with ALL. Flow cytometry was performed to monitor MRD occurrence during treatment. Results: Of 1030 patients with MRD-negative results, 150 (14.6%) showed MRD re-emergence while still on morphological complete remission (CR). Patients with white blood cell counts of ≥50 × 109/L (p = 0.033) and MRD levels of ≥0.1% on day 33 (p = 0.012) tended to experience MRD re-emergence. The median re-emergent MRD level was 0.12% (range, 0.01–10.00%), and the median time to MRD re-emergence was 11 months (range, <1–52 months). Eighty-five (56.6%) patients subsequently developed relapse after a median of 4.1 months from detection of MRD re-emergence. The median re-emergent MRD level was significantly higher in the relapsed cohort than in the cohort with persistent CR (1.05% vs. 0.48%, p = 0.005). Of the 150 patients, 113 continued to receive chemotherapy and 37 underwent transplantation. The transplantation group demonstrated a significantly higher 2-year overall survival (88.7 ± 5.3% vs. 46.3 ± 4.8%, p < 0.001) and cumulative incidence of relapse (23.3 ± 7.4% vs. 64.0 ± 4.6%, p < 0.001) than the chemotherapy group. Conclusions: MRD re-emergence during treatment was associated with an adverse outcome in pediatric ALL patients. Transplantation could result in a significant survival advantage for these patients.